Decisões econômicas e formulação de políticas públicas: influência de vieses cognitivos e biológicos - Amaral, Pedro Henrique Rincon (2019)
The behavioral economy has focused on the study of how human behavior may deviate from the rationality stated by the economy principles. In this sense, identifying and taking into consideration the biases of individuals whose behavior is regulated by the State may increase the effectiveness of policymaking processes, while addressing policymakers biases is fundamental to guarantee that state intervention will not produce inefficient or biased regulation as a result of human bounded rationality. The recent literature has pointed out that the hormone testosterone is correlated to decision making of the economic agents under a risky environment. This paper aims at identifying the most common biases to which public regulators and regulated individuals are subject and both to point out methods which could be used to mitigate its effects on the regulatory dynamics and to foster experiments that observe the existence and persistence of biases on individuals. Finally, it was possible to fulfill a remaining gap on Brazilian literature on how cognitive and biological bias may affect a rational agent’s decision and contribute to scientific knowledge when evidencing possible impacts to public regulation from such bias in a way to make it inefficient, unnecessary and even unfair, and that it is necessary to rethink the decision-making architecture of such actors in order to incorporate structures bias correction tools.